Critique does not equate to rebellion: Positive deviance and entrepreneurial networking among small and medium enterprises in Uganda - Mayanja, Samuel; Ntayi, Joseph M.; Munene, J. C.; Wasswa, Balunywa; Kibirango, Moses M. (African Journal of Business Management, 2019)
This paper examines the relationship between positive deviance and entrepreneurial networking among small and medium enterprises (SMEs). Using a mixed method approach combined self-administered questionnaires and interview guide covering 228 SMEs in Uganda, the cross-sectional nature of this study revealed key nuances about SMEs. The research findings confirmed a significant positive relationship between positive deviance and entrepreneurial networking among SMEs in Uganda. The findings also revealed that: SME owner/ managers should create enabling environment for people with divergent views to interact with each other to innovate new practices, such as accessing resources from the networks; managers should initiate new policies for error management to allow employees room to learn from mistakes; managers should acquire new skills of leadership skills to manage and utilize the knowledge and skills of positive deviants. This research therefore contributes to existing scholarship by providing nuances in the study of positive deviance and entrepreneurial networking among SMEs in Uganda through employing a complexity approach that transcends previous academic focus on social network theory.
Keywords: Positive deviance; Entrepreneurial networking; Small and medium enterprises (SMEs); Complexity